UJI KUALITAS FISIS PENGOLAHAN LIMBAH PLASTIK MENJADI BAHAN BAKAR ALTERNATIF - Rahmaniah Rahmaniah; Nurhalimah Nurhalimah; Sahara Sahara (Teknosains, 2016)
This study aims to determine whether the plastic waste can be usedas an alternative fuel and to determine the physical quality of alternativefuels plastic waste generated before distillation and after distillation. Thisstudy is done the combustion process using a tool designed himself. After theburning process, the oil obtained is done by testing physical parameters aredensity, viscosity and caloric value. The results showed that the physicalquality of alternative fuels, namely plastic waste For this type of plasticPET, HDPE, LDPE, PVC and PP in density test results obtained before andafter distillation not meet fuel standards. The results obtained on testing theviscosity value for the type of plastic PET, LDPE, PP and PVC beforedistillation including kerosene fuel standards. Whereas For this type ofplastic HDPE and PP after distillation including kerosene fuel standards.While the test results obtained calorific values for the type of plastic PET,HDPE, PVC, LDPE and PP before and after distillation not meet fuelstandards.